On Construction of D-Focal Curves in Euclidean 3-Space M3 - Asil, Vedat; Bas, Selcuk; Korpinar, Talat (Soc Paranaense Matematica, 2013)
In this paper, we study D-focal curves in the Euclidean 3-space M-3. We characterize D-focal curves in terms of their focal curvatures.
Keywords: Darboux frame; Euclidean 3-space; Focal curve; Normal curvature; Geodesic Curvature; Geodesic torsion